간호대학생 대상의 국제보건역량강화 프로그램 효과: 체계적 문헌고찰 및 메타분석 - 박서아; Park Seo A; 김혜영; Kim Hye Young (글로벌 건강과 간호, 2022)
Purpose: This study aimed to evaluate the effects of global health competency education on cultural competence, empathy, and cultural acceptance among nursing students in Korea. Methods: A literature review was performed until July 2021 in domestic electronic databases, including KoreaMed, RISS, KISS, and Google Scholar. Nine references that met the inclusion and exclusion criteria were selected and Meta-analysis was performed using Cochrane’s risk of bias tool and the R version 3.5.2 (Meta-analysis with R) program. Results: The findings in this study indicate that effect size of global health competency education for cultural competence was Hedges'g=1.33 (95% confidence interval, 0.78~1.89) and the effect size of empathy was Hedges'g=0.82 (95% confidence interval, 0.07~1.57), as indicated by a large effect size. The effect size of cultural acceptance was Hedges'g=0.49 (95% confidence interval, 0.06~0.92), as indicated by a moderate effect size. The differences were statistically significant. In the meta-subgroup analyzed by approach intervention type, intervention time had a significant effect. The risk of publication bias is low. This study found that the global health competency education program for nursing students had an effect on cultural competence, empathy, and cultural acceptance. Conclusion: Various global health competency programs should be developed and implemented for nursing students to improve their multicultural health competencies.